2014
DOI: 10.1007/s40622-014-0067-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of corporate governance score on abnormal returns and financial performance of mergers and acquisitions

Abstract: The present study attempts to investigate whether differences in the quality of firm level corporate governance standards influence performance of acquiring firms for a sample of companies by creating a corporate governance index. The study is based on a survey of sample of 155 companies having completed mergers and acquisitions deals announced during January 2003-December 2008. The paper analyzes the relationship between corporate governance practices of the acquiring firms and abnormal returns during event w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 70 publications
0
8
0
Order By: Relevance
“…From the agency theory perspective, guidelines for the relationships between managers and owners are warranted; they should protect shareholders' interests through implementing codes of good governance. The agency theory suggests that a bettergoverned firm should demonstrate superior performance due to lower agency costs (Rani et al, 2014;Sami et al, 2011). However, there is no consensus in the existing literature with regard to how corporate governance or performance outcomes should be measured.…”
Section: Corporate Governance and Firm Performancementioning
confidence: 99%
“…From the agency theory perspective, guidelines for the relationships between managers and owners are warranted; they should protect shareholders' interests through implementing codes of good governance. The agency theory suggests that a bettergoverned firm should demonstrate superior performance due to lower agency costs (Rani et al, 2014;Sami et al, 2011). However, there is no consensus in the existing literature with regard to how corporate governance or performance outcomes should be measured.…”
Section: Corporate Governance and Firm Performancementioning
confidence: 99%
“…The corporate governance, especially board structure is important during the economic recession period, as it is board that control on the decision making and strategic direction which has a decisive bearing on firm's performance (O'Connell and Cramer, 2010;Rani et al, 2014). A company having better corporate governance structure and practices derives better valuations (Rani et al, 2014;Reddy, 2015). This study examines the efficacy of the board of directors on firm performance during the period of financial crisis.…”
Section: Introductionmentioning
confidence: 99%
“…Majority of corporate governance studies in India are linked with financial performance (e.g., Arora & Sharma, 2016;Bansal & Sharma, 2016;Bhatt & Bhattacharya, 2015;Kandukuri et al, 2015;Mishra & Mohanty, 2014;Palaniappan, 2017;Rani et al, 2014;Sanan, 2016;Singla & Singh, 2019;Yameen et al, 2019). The results of these studies are inconsistent and the findings are conflicted in some cases.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of these studies are inconsistent and the findings are conflicted in some cases. Some studies reported that there is an association between corporate governance indicators and financial performance (Arora & Sharma, 2016;Kandukuri et al, 2015;Rani et al, 2014). Some other studies revealed that some corporate governance attributes only have a positive influence on firms' performance; larger board size and attendance of the board members (Bhatt & Bhattacharya, 2015), promoters' ownership (Mishra & Kapil, 2017), board age diversity (Kagzi & Guha, 2018), board size and CEO Chairman dual role (Bansal & Sharma, 2016), independent women directors (Sanan, 2016), board independence, board size and busyness (Mishra & Kapil, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%